Fostering Social Development through Partnership between Mining Companies and Local Communities - Fadri, Zainal; Gilang Prayoga, Andhika; Amadou Diallo, Thierno (Komunitas: International Journal of Indonesian Society and Culture, 2025)
This research focuses on community development through collaboration with mining companies. Many communities claim to have not received benefits from the presence of companies in their areas, necessitating a study on joint potential development activities. The purpose of this research is to create a social potential mapping that will be used in formulating and determining policies to enhance potential. This research employs a mixed-methods approach, combining both quantitative and qualitative methods. Quantitative approaches are used to analyze statistical data collected in the field, while qualitative approaches are used to conduct in-depth analyses of social problems and determine policy directions for developing social potential in the area. This research was conducted in Kampung Enam, Kalimantan. The results of this study indicate that there are many social potentials that can be developed to improve social quality, and that companies can work together to formulate policies or plans for further development. Companies have shown great interest and commitment to the development of local communities, enabling recommendations for community development programs to be implemented according to community needs.